2013
DOI: 10.1002/jat.2966
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressant tributyltin oxide blocks the mTOR pathway, like rapamycin, albeit by a different mechanism

Abstract: We treated the thymoma cell line (EL4) with two model immunosuppressants, rapamycin and tributyltin oxide (TBTO), and compared their effects on the expression levels of proteins that are downstream targets of mTOR kinase 1 (mammalian target of rapamycin, known also as mechanistic target of rapamycin): p70 ribosomal S6 kinase1 and 4E-binding protein 1, a repressor of the cap-binding protein eIF4E. In addition, we evaluated the levels of ribosomal protein S6, p-eIF4B, substrates of p70S6 kinase1, matrin 3 and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Several studies have shown that harmful internal and external factors can decrease oocyte quality and in turn reduce embryonic developmental competence ( Liang et al, 2017b ; Nie et al, 2019 ; Sun et al, 2020 ). The negative effects of TBTO exposure on different types of cells in different species, especially germ cells, have also been reported ( Baken et al, 2007 ; Mochida et al, 2007 ; Osman and van Loveren, 2012 , 2014 ). Previous research has suggested that TBTO exposure impairs mouse oocyte quality by inducing mitochondrial dysfunction, oxidative stress and apoptosis, thus causing abnormal spindle organization and chromosome alignment and eventually resulting in fertility failure ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have shown that harmful internal and external factors can decrease oocyte quality and in turn reduce embryonic developmental competence ( Liang et al, 2017b ; Nie et al, 2019 ; Sun et al, 2020 ). The negative effects of TBTO exposure on different types of cells in different species, especially germ cells, have also been reported ( Baken et al, 2007 ; Mochida et al, 2007 ; Osman and van Loveren, 2012 , 2014 ). Previous research has suggested that TBTO exposure impairs mouse oocyte quality by inducing mitochondrial dysfunction, oxidative stress and apoptosis, thus causing abnormal spindle organization and chromosome alignment and eventually resulting in fertility failure ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
“…As TBTO is a model immune poison, TBTO exposure can inhibit chemotaxis associated with the chemokine CXCL12, thereby affecting the migration of white blood cells ( Shao et al, 2016 ). In addition, TBTO exposure can reduce the immunotoxicity of interleukin 2 by blocking the mTOR pathway ( Osman and van Loveren, 2014 ). Research has shown that TBTO exposure affects proliferation and energy sensor pathways by downregulating MAPK, matrin-3 and the ribonucleotide reductase subunit RRM2, which are implicated in cell proliferation in mouse thymoma cells ( Osman and van Loveren, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with the previously reported findings by Osman and van Loveren (2012) that TBTO down-regulated the expression level of phosphorylated p70S6K in the EL4 mouse thymoma line. In addition, recent results from Osman and van Loveren (2013) showed that, although TBTO dephosphorylated p70S6K, the phosphorylation of the other downstream effector of mTORC1, 4EBP1, was induced by TBTO, whereas rapamycin dephosphorylated this protein. This result also indicated that dephosphorylation of p70S6K by TBTO was independent of mTOR.…”
Section: Discussionmentioning
confidence: 95%
“…Osman et al figured out TBTO inhibits EL4 cells proliferation by impairing protein synthesis about cell structure and cytoskeleton. To fully understand the underlying mechanism, microarray studies and phosphor proteomic analysis have been conducted and researchers figure out that TBTO affects mammalian target of rapamycin signaling pathway first, further influences energy pathways and cell proliferation . Except for the immunotoxicity effect, TBTO also causes adverse effects to vertebrate and invertebrate endocrine systems and endocrine disruption .…”
Section: Introductionmentioning
confidence: 99%
“…To fully understand the underlying mechanism, microarray studies and phosphor proteomic analysis have been conducted and researchers figure out that TBTO affects mammalian target of rapamycin signaling pathway first, further influences energy pathways and cell proliferation. 14 Except for the immunotoxicity effect, TBTO also causes adverse effects to vertebrate and invertebrate endocrine systems and endocrine disruption. 15 Otherwise, reactive oxygen species (ROS) in the liver of rats exposed to TBTO is increased significantly.…”
mentioning
confidence: 99%